Gothic passages : racial ambiguity and the American gothic - Edwards, Justin D., 1970- (Iowa City : University of Iowa Press, 2003)
This groundbreaking study analyzes the development of American gothic literature alongside nineteenth-century discourses of passing and racial ambiguity. By bringing together these areas of analysis, Justin Edwards considers the following questions. How are the categories of "race" and the rhetoric of racial difference tied to the language of gothicism? What can these discursive ties tell us about a range of social boundaries - gender, sexuality, class, race, etc. - during the nineteenth century? What can the construction and destabilization of these social boundarie
Hybrid bodies and gothic narratives in Poe's Pym -- Gothic travels in Melville's Benito Cereno -- Passing and abjection in William and Ellen Craft's Running a thousand miles for freedom -- The epistemology of the body; or, gothic secrets in Frances E.W. Harper's Iola Leroy -- Genetic atavism and the return of the repressed in William Dean Howell's An imperative duty -- The haunted house behind the cedars: Charles W. Chesnutt and the "white negro" -- Epilogue: twentieth-century gothicism and racial ambiguity.
Includes bibliographical references (pages 123-139) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Horror tales, American -- History and criticism; American fiction -- 19th century -- History and criticism; Gothic revival (Literature) -- United States; Multiracial people in literature; Passing (Identity) in literature; Ambiguity in literature; Race in literature; Récits d'horreur américains -- Histoire et critique; Roman américain -- 19e siècle -- Histoire et critique; Littérature frénétique -- États-Unis.; Passing (Identité) dans la littérature.; Ambiguïté dans la littérature.; Race dans la littérature.; LITERARY CRITICISM -- American -- General; Ambiguity in literature; American fiction; Gothic revival (Literature); Horror tales, American; Passing (Identity) in literature; Race in literature; Multiracial people in literature; United States; Gothic Revival (letterkunde); Amerikaans; Letterkunde; Rassenverhoudingen; 1800-1899; Criticism, interpretation, etc